Bioarchaeological analysis of an anencephalic fetus from the archaeological site cueva de los ninos (ultima esperanza, magallanes, chile): 29 years after its discovery Análisis bioarqueológico de un feto anencefálico del sitio arqueológico cueva de los niños (provincia de última esperanza, región de magallanes, Chile): A 29 años de su hallazgo - Palacios C., Cristóbal; Sierpe Gonzalez, Victor Manuel (My University, 2019)
The re-evaluation of human bones from the Cueva de los Ninos site located in the province of Ultima Esperanza, Chile, is presented. This work focuses on deepening the analysis of the anencephalic fetus called Ultima Esperanza A, sustained by the availability of new methods for the analysis of bone material and by the presence of unstudied remains from the individual. After estimating the age using new regression equations and considering the alterations produced by fetal neurological defects in the development of long bones, we suggest the possibility that the age of the fetus is between one or two weeks less than that proposed previously. New bioanthropological data on the individual are provided, emphasizing its importance and the few documented cases of anencephalic fetuses found in archaeological contexts worldwide. Finally, the possibility that the individual Ultima Esperanza A and the other fetus found at the site (Ultima Esperanza B) were born from a multiple pregnancy is discussed, based on the possible lower age difference between them and the higher incidence of anencephaly in these cases.
Keywords: anencephaly; bioarchaeology; multiple pregnancy; patagonia; twins